E-Modules of Natural and Social Sciences (IPAS) “Changes in Energy Forms” with FlipHTML5 to Improving the Student Motivation of Elementary School - Yowanti Laela Isnaeni; Zulherman (Jurnal Penelitian Pendidikan IPA, 2024)
In grade IV, students continue to show low learning in learning materials at school, especially in IPAS material. many things that cause one of them is learning media that is still conventional. This study aims to develop a FlipHTML5-assisted electronic module with the aim of improving learning outcomes and motivation. By combining R&D methodology with the ADDIE development concept. With an average result from material validators of 70% which included the “Feasible” category, an average result from media validators of 96%, which included the “Very Feasible” category, and an average result from language validators of 85%, which included the “Very Feasible” category, the findings showed that implementing electronic learning modules with the support of FlipHTML5 was very feasible. By evaluating the effectiveness of FlipHTML5-assisted E-Modules in IPAS subjects and calculating N-Gain and t-test values to determine differences from experimental and control groups, this research has helped in the development of teaching materials and is effectively used in the learning process. The results of the analysis show that the development of electronic modules is feasible, which aims to motivate students to learn.